2012
DOI: 10.1016/j.pnpbp.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid modulation of noradrenergic circuits: Implications for psychiatric disorders

Abstract: The interaction between the endocannabinoid system and catecholaminergic circuits has gained increasing attention as it is recognized that the development of synthetic cannabinoid receptor agonists/antagonists or compounds targeting endocannabinoid synthesis/metabolism may hold some therapeutic potential for the treatment of psychiatric disorders. The noradrenergic system plays a critical role in the modulation of emotional state, primarily related to anxiety, arousal, and stress. Recent evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 122 publications
(190 reference statements)
0
50
0
1
Order By: Relevance
“…***p<0.001 compared with saline, +p<0.05, and +++p<0.001 compared with their respective groups. cannabinoid tone controls LC activity (Carvalho and Van Bockstaele, 2012). Unfortunately, few studies have focused on the interaction of cannabinoids and norepinephrine on the cellular level, although there are abundant data about the action of cannabinoids on complex changes of behavior mediated by the monoaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…***p<0.001 compared with saline, +p<0.05, and +++p<0.001 compared with their respective groups. cannabinoid tone controls LC activity (Carvalho and Van Bockstaele, 2012). Unfortunately, few studies have focused on the interaction of cannabinoids and norepinephrine on the cellular level, although there are abundant data about the action of cannabinoids on complex changes of behavior mediated by the monoaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cerebellum has minimal DA innervation, which suggests that reduced metabolic increases to MP in CA could also reflect attenuated reactivity to MP-induced noradrenergic stimulation (Tilley and Gu, 2008). The cannabinoid system is an important regulator of noradrenergic systems in part via CB1 receptors (Reyes et al, 2009;Carvalho and Van Bockstaele, 2012;Cathel et al, 2014) and downregulation of CB1 receptors in CA (Hirvonen et al, 2012) could underlie the attenuated responses to MP-induced changes in metabolism observed in these brain regions. A prior study in CA showed that co-administration of Δ-9-tetrahydrocannabinol (THC) with ecstasy, which like MP is a monoamine transporter blocker, enhanced its cardiovascular effects and the increases in epinephrine and norepinephrine in plasma (Dumont et al, 2009).…”
Section: Effects Of Mp On Brain Metabolism In Ca and Hcmentioning
confidence: 99%
“…Both of the known cannabinoid receptors are coupled to Gα i/o , which is negatively coupled to adenylyl cyclase activity and downregulates cAMP production. CB 1 receptors are localized primarily on the presynaptic terminals of glutamatergic and GABAergic synapses, where they reduce the release probabilities of glutamate and GABA and modulate excitatory and inhibitory neurotransmission (Di, Malcher-Lopes, Halmos, & Tasker, 2003;Hirasawa et al, 2004;Melis et al, 2004;Ohno-Shosaku et al, 2002;, although they have also been reported to modulate the release of other neurotransmitters, such as norepinephrine (Carvalho & Van Bockstaele, 2012). Activation of presynaptic CB 1 receptors has been shown to suppress calcium influx via presynaptic voltage-gated calcium channels (Wilson, Kunos, & Nicoll, 2001), and to facilitate the opening of presynaptic voltage-gated potassium channels (Mackie, Lai, Westenbroek, & Mitchell, 1995), which lead in both cases to a decrease in the probability of neurotransmitter release.…”
Section: The Endocannabinoids and Their Receptorsmentioning
confidence: 99%